YOGYAKARIA KOTA PENDIDIKAN DAN EKONOMI ALTERNATIF - Sugiyanto Sugiyanto (Jurnal Cakrawala Pendidikan, 2004)
Yogyakarta is regarded as a city ofeducation, culture, and tourism. However, the government, bureaucracy, stake holders, and king of the acknowledged kingdom of Yogyakarta himself, as head of the Yogyakarta Special Territory, have cautioned everybody to beware that the increasing Realization of the importance ofeducation has brought the city of Yogyakarta to becoming known as the·"city of education throughout the Indonesian archipelago. ; One of the positive effects of being given the attribute of the city of education is the birth of alternative forms of economic activities conducted there by people from any social class, high, middle, and low alike. Some negative effects are that the city has also become one of the targets for drug transactions, free lifestyles in boardinghouses, and high rates of traffic violations related to disregard ofand disobedience to traffic signs. The recent passing ofthe 1999 State Law No. 22 has nevertheless warned the city of its continuing existence as the city of education. It provides the country with regional autonomy and one of its effects has been the emergence of private universities in every regency. It is predicted that it would lessen the number of people coming to the city of Yogyakarta to study at its universities. If it happens, the alternative forms of economic activities might disappear because most of the customers are university students.